Senior citizen and online form: hybrid guideline form design / Zanariah Idrus ... [et al.] - Idrus, Zanariah; Abdul Razak, Nor Hafizah; Abdul Talib, Noor Hasnita (2015)
The World Health Organization predicts by year 2020, senior citizens population will be more than 1 billion. They are progressively exposed to technology and to understand their requirements is significant in human interface design. But, the online form interface design tends to ignore the issue of ease of use especially for senior citizens aged 60 and above. A well known Delivering Inclusive Access to Disabled and Elderly Members (DIADEM) guideline outlines the recommended online form design for the senior citizens. DIADEM is specifically tailored for senior citizens with age 65 and above only and not relevant for Malaysia culture. WeFDeC guideline aligns the online form design based on the Three Layer Model (Perceptual, Conversational and Relationship layers). Though it is an acceptable guideline for online form but it does not take senior citizens into consideration. Therefore, this study compared WeFDeC and DIADEM guideline, identify the weakness and create a new hybrid guideline. The new hybrid guideline (Elder-WeFDe) which should fit with senior citizens online forms was introduced. This guideline is relevant for different purpose of online forms; application, services and e-commerce. It also able to guide web or online form designers to design a better and ease of use online forms for the senior citizens as well as for all age of groups.